LITERATURE REVIEW ON MANAGEMENT CONSULTING COLLABORATION WITH COMPANIES WHILE CRAFTING STRATEGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The literature review aims to explore how companies collaborate with management consulting service providers. Also, the review identifies collaboration impact on company’s strategy and encompasses relevant theories and research results performed and developed in the field of management consulting, strategy and its development over decades as a supportive service for companies.Literature review results are obtained with qualitative methods - by exploring insight from diverse selection of works covering management consulting and competitive strategy. Insights are analyzed by revealing patterns of how management consulting providers use their expertise to help their clients - various size companies in their path to craft the strategy or solve business related problems. Also, how management consulting firms identify their strategy-as-practice niche and create perception of value creation ability for clients.Research results indicate a connection between management consulting services and strategy as a service and practice and need for external knowledge and experience-based expertise. Findings indicate that for small and medium-sized companies it is often hard to craft and implement a competitive strategy with limited resources and inner management solution generating and executing capacity.  Struggles that companies will face on the transformative path are decision taking in solving problems, change of a business model and setting up overall strategic direction and goals.Research limitations relate to companies that experience struggle of how to craft strategies in collaboration with management consulting services that are provided by professionals that work with various size companies and industries.; The value of this paper is a literature review that covers up-to-date knowledge of what is known and what should be more deeply explored. Review includes the indication and collaboration opportunity direction of how to create a competitive strategy for various and especially small and medium-sized enterprises in modern business world. Paper can be used further for creating a theoretical model of how and when to efficiently use the management consulting services globally and is their actual impact.